The development of knowledge management system for public higher learning in collaborative environment using lotus notes software - Rusli Abdullah; Shamsul Sahibuddin; Rose Alinda Alias, 1964-; Mohd. Hasan Selamat; Knowledge Management International Conference and Exhibition (2004 : Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 2004)
28